Health Education Tentang Pentingnya Pola Hidup Sehat pada Wanita Menopuse - Mukarrama Mukarrama; Siti Maimunah; Zesika Intan Novelia (Jurnal Pelayanan Masyarakat, 2025)
Menopause is a natural phase in a woman's life marked by the permanent cessation of the menstrual cycle, usually occurring at the age of 45-55 years. This period is often accompanied by various physical and psychological changes that can interfere with the quality of life. Education about healthy lifestyles is very important to help menopausal women manage symptoms and prevent long-term health complications. This community service activity aims to provide health education related to healthy lifestyles to menopausal women in Simpursia Village, Wajo Regency. In the menopause phase, decreased estrogen and progesterone hormones can cause various psychological symptoms such as fear of getting old, being unattractive, difficulty sleeping, getting angry easily, being very emotional, feeling depressed and sad for no apparent reason, fear of losing a husband. If left untreated, this condition can cause the elderly to experience anxiety and depression which will affect the quality of life. The methods used are counseling, interactive discussions, The results of the activity showed an increase in participants' understanding of the importance of balanced nutrition, physical activity, stress management, and routine health checks. Health education has been proven effective in increasing awareness and healthy living behavior in menopausal women.